This is a short, fast and analogy-free introduction to Haskell monads derived from a categorical perspective. This assumes you are familiar with Haskell and basic category theory.

*If you aren’t already comfortable with monads in Haskell, please don’t read this. It will confuse your intuition even more.*

We have a abstract **category** \(\mathcal{C}\) which consists of objects and morphisms.

- Objects : \(●\)
- Morphisms : \(● \rightarrow ●\)

For each object there is an identity morphism `id`

and a composition rule \((\circ)\) for combining morphisms associatively. We can model this with the following type class in Haskell with kind polymorphism.

```
-- Morphisms
type (a ~> b) c = c a b
class Category (c :: k -> k -> *) where
id :: (a ~> a) c
(.) :: (y ~> z) c -> (x ~> y) c -> (x ~> z) c
```

In Haskell we call this cateogry *Hask*, over the type constructor `(->)`

of function types between Haskell types.

```
type Hask = (->)
instance Category Hask where
id x = x
(f . g) x = f (g x)
```

The constructor `(->)`

is sometimes confusing to read in typeclass signatures as a typelevel operator since it’s first argument usually appears to the left of it in infix form and the second to the right. For example the following are equivalent.

`(->) ((->) a b) ((->) a c)`

`(a -> b) -> (a -> c)`

Between two categories we can construct a **functor** denoted \(T\), which maps between objects and morphisms of categories that preserves morphism composition and identities.

- Objects : \(T(●)\)
- Morphisms : \(T (● \rightarrow ●)\)

Represented in Haskell by:

```
class (Category c, Category d) => Functor c d t where
fmap :: c a b -> d (t a) (t b)
```

With the familiar functors laws:

```
fmap id ≡ id
fmap (a . b) ≡ (fmap a) . (fmap b)
```

The identity functor \(1_\mathcal{C}\) for a category \(\mathcal{C}\) is a functor mapping all objects to themselves and all morphisms to themselves.

```
newtype Id a = Id a
instance Functor Hask Hask Id where
fmap f (Id a) = Id (f a)
instance Functor Hask Hask [] where
fmap f [] = []
fmap f (x:xs) = f x : (fmap f xs)
instance Functor Hask Hask Maybe where
fmap f Nothing = Nothing
fmap f (Just x) = Just (f x)
```

An **endofunctor** is a functor from a category to itself, i.e. (\(T : \mathcal{C} \to \mathcal{C}\)).

`type Endofunctor c t = Functor c c t`

The composition of two functors is itself a functor as well. Convincing Haskell of this fact requires some trickery with constraint kinds and scoped type variables.

```
newtype FComp g f x = C { unC :: g (f x) }
newtype Hom (c :: * -> Constraint) a b = Hom (a -> b)
instance (Functor a b f, Functor b c g, c ~ Hom k) => Functor a c (FComp g f) where
fmap f = (Hom C) . (fmapg (fmapf f) . (Hom unC))
where
fmapf = fmap :: a x y -> b (f x) (f y)
fmapg = fmap :: b s t -> c (g s) (g t)
```

The repeated composition of an endofunctor over a category is written with exponential notation:

\[ \begin{align*} T^2 &= T T : \mathcal{C} \rightarrow \mathcal{C} \\ T^3 &= T T T: \mathcal{C} \rightarrow \mathcal{C} \end{align*} \]

The category of small categories \(\textbf{Cat}\) is a category with categories as objects and functors as morphisms between categories.

For two functors \(F,G\) between two categories \(\mathcal{A,B}\):

\[ F : \mathcal{A} \rightarrow \mathcal{B} \\ G : \mathcal{A} \rightarrow \mathcal{B} \]

We can construct a mapping called a **natural transformation** \(\eta\) which is a mapping between functors \(\eta : F \rightarrow G\) that associates every object \(X\) in \(\mathcal{A}\) to a morphism in \(\mathcal{B}\):

\[ \eta_X : F(X) \rightarrow G(X) \]

Such that the following *naturality condition* holds for any morphism \(f : X \rightarrow Y\). Shown as a *naturality square*:

\[ \eta_Y \circ F(f) = G(f) \circ \eta_X \]

The natural transformation itself is shown diagrammatically between two functors as:

This is expressible in our general category class as the following existential type:

`type Nat c f g = forall a. c (f a) (g a)`

In the case of *Hask* we a family of polymorphic functions with signature:

`type NatHask f g = forall a. (f a) -> (g a)`

With the naturality condition as the following law for a natural transformation (`h`

), which happens to be a free theorem in Haskell’s type system.

`fmap f . h ≡ h . fmap f `

The canonical example is the natural transformation between the List functor and the Maybe functor ( where f = `List`

, g = `Maybe`

).

```
headMay :: forall a. [a] -> Maybe a
headMay [] = Nothing
headMay (x:xs) = Just x
```

Either way we chase the diagram we end up at the same place.

`fmap f (headMay xs) ≡ headMay (fmap f xs)`

Run through each of the cases of the naturality square for `headMay`

if you need to convince yourself of this.

```
fmap f (headMay [])
= fmap f Nothing
= Nothing
headMay (fmap f [])
= headMay []
= Nothing
```

```
fmap f (headMay (x:xs))
= fmap f (Just x)
= Just (f x)
headMay (fmap f (x:xs))
= headMay [f x]
= Just (f x)
```

A natural transformation \(\eta : C \rightarrow D\) is itself a morphism in the **functor category** \(\textbf{Fun}(\mathcal{C}, \mathcal{D})\) of functors between \(\mathcal{C}\) and \(\mathcal{D}\). The category \(\textbf{End}\) is the category of endofunctors between a category and itself.

```
-- Functor category
newtype Fun f g a b = FNat (f a -> g b)
-- Endofunctor category
type End f = Fun f f
instance Category (End f) where
id = FNat id
(FNat f) . (FNat g) = FNat (f . g)
```

We can finally define a *monad* over a category \(\mathcal{C}\) to be a triple \((T, \eta, \mu)\) of:

- An endofunctor \(T: \mathcal{C} \rightarrow \mathcal{C}\)
- A natural transformation \(\eta : 1_\mathcal{C} \rightarrow T\)
- A natural transformation \(\mu : T^2 \rightarrow T\)

```
class Endofunctor c t => Monad c t where
eta :: c a (t a)
mu :: c (t (t a)) (t a)
```

With an associativity square:

\[ \mu \circ T \mu = \mu \circ \mu T \\ \]

And a triangle equality:

\[ \mu \circ T \eta = \mu \circ \eta T = 1_C \\ \]

Alternatively we can express our triple as a series of **string diagrams** in which we invert the traditional commutative diagram of lines as morphism and objects as points and morphisms as points and objects as lines. In this form the monad laws have a nice geometric symmetry.

With the coherence conditions given diagrammatically:

There is an equivalent formulations of monads in terms of two functions (`(>>=), return`

) which can be written in terms of `mu, eta`

)

In Haskell we define a bind `(>>=)`

operator defined in terms of the natural transformations and `fmap`

of the underlying functor. The `join`

and `return`

functions can be defined in terms of `mu`

and `eta`

.

```
(>>=) :: (Monad c t) => c a (t b) -> c (t a) (t b)
(>>=) f = mu . fmap f
return :: (Monad c t) => c a (t a)
return = eta
```

In this form equivalent naturality conditions for the monad’s natural transformations give rise to the regular monad laws by substitution with our new definitions.

```
fmap f . return ≡ return . f
fmap f . join ≡ join . fmap (fmap f)
```

And the equivalent coherence conditions expressed in terms of bind and return are the well known Monad laws:

```
return a >>= f ≡ f a
m >>= return ≡ m
(m >>= f) >>= g ≡ m >>= (\x -> f x >>= g)
```

The final result is given a monad we can form a new category called the *Kleisli category* from the monad. The objects are embedded in our original `c`

category, but our arrows are now Kleisli arrows `a -> T b`

. Given this class of “actions” we’d like to write an operator which combined these morphisms just like we combine functions in our host category.

\[ \begin{align} & (b \to T c) \to (a \to T b) \to (a \to T c) \\ & (b \to c) \to (a \to b) \to (a \to c) \end{align} \]

In turns we out can for a specific function `(<=<)`

expressed in terms of \(\mu\) and the underlying functor, which gives associative composition operator of Kleisli arrows. The Kleisli category models “composition of actions” and form a very general model of computation.

The mapping between a Kleisli category formed from a category \(\mathcal{C}\) is that:

- Objects in the Kleisli category are objects from the underlying category.
- Morphisms are Kleisli arrows of the form : \(f : A \rightarrow T B\)
- Identity morphisms in the Kleisli category are precisely \(\eta\) in the underlying category.
- Composition of morphisms \(f \circ g\) in terms of the host category is defined by the mapping:

\[ f \circ g = \mu ( T f ) g \]

```
-- Kleisli category
newtype Kleisli c t a b = K (c a (t b))
-- Kleisli morphisms ( c a (t b) )
type (a :~> b) c t = Kleisli c t a b
-- Kleisli morphism composition
(<=<) :: (Monad c t) => c y (t z) -> c x (t y) -> c x (t z)
f <=< g = mu . fmap f . g
instance Monad c t => Category (Kleisli c t) where
-- id :: (Monad c t) => c a (t a)
id = K eta
-- (.) :: (Monad c t) => c y (t z) -> c x (t y) -> c x (t z)
(K f) . (K g) = K ( f <=< g )
```

In the case of Hask where `c = (->)`

we see the usual instances:

```
-- Kleisli category
newtype Kleisli m a b = K (a -> m b)
-- Kleisli morphisms ( a -> m b )
type (a :~> b) m = Kleisli m a b
(<=<) :: Monad m => (b -> m c) -> (a -> m b) -> a -> m c
f <=< g = mu . fmap f . g
instance Monad m => Category (Kleisli m) where
id = K return
(K f) . (K g) = K (f <=< g)
```

```
class Functor t where
fmap :: (a -> b) -> t a -> t b
class Functor t => Monad t where
eta :: a -> (t a)
mu :: t (t a) -> (t a)
(>>=) :: Monad t => t a -> (a -> t b) -> t b
ma >>= f = join . fmap f
```

*Stated simply that the monad laws above are just the category laws in the Kleisli category*, specifically the monad laws in terms of the Kleisli category of a monad `m`

are:

```
(f >=> g) >=> h ≡ f >=> (g >=> h)
return >=> f ≡ f
f >=> return ≡ f
```

For example, `Just`

is just an identity morphism in the Kleisli category of the `Maybe`

monad.

```
Just >=> f = f
f >=> Just = f
```

```
just :: (a :~> a) Maybe
just = K Just
left :: forall a b. (a :~> b) Maybe -> (a :~> b) Maybe
left f = just . f
right :: forall a b. (a :~> b) Maybe -> (a :~> b) Maybe
right f = f . just
```

For instance the **List monad** would have have:

- \(\eta\) returns a singleton list from a single element.
- \(\mu\) turns a nested list into a flat list.
- \(\mathtt{fmap}\) applies a function over the elements of a list.

```
instance Functor [] where
-- fmap :: (a -> b) -> [a] -> [b]
fmap f (x:xs) = f x : fmap f xs
instance Monad [] where
-- eta :: a -> [a]
eta x = [x]
-- mu :: [[a]] -> [a]
mu = concat
```

The **Maybe monad** would have:

- \(\eta\) is the Just constructor.
- \(\eta\) combines two levels of Just constructors yielding the inner value or Nothing.
- \(\mathtt{fmap}\) applies a function under the Just constructor or nothing for Nothing.

```
instance Functor [] where
-- fmap :: (a -> b) -> Maybe a -> Maybe b
fmap f (Just x) = Just (f x)
fmap f Nothing = Nothing
instance Monad Maybe where
-- eta :: a -> Maybe a
eta x = Just x
-- mu :: (Maybe (Maybe a)) -> Maybe a
mu (Just (Just x)) = Just x
mu (Just Nothing) = Nothing
```

The **IO monad** would intuitively have the implementation:

- \(\eta\) returns a pure value to a value within the context of the computation.
- \(\mu\) turns a sequence of IO operation into a single IO operation.
- \(\mathtt{fmap}\) applies a function over the result of the computation.

```
instance Functor IO where
-- fmap :: (a -> b) -> IO a -> IO b
instance Monad Maybe where
-- eta :: a -> IO a
-- mu :: (IO (IO a)) -> IO a
```